DESAIN PEMBELAJARAN MATEMATIKA BERBANTUAN MATH MAZE UNTUK MEMFASILITASI RETENSI DAN MINAT BELAJAR PESERTA DIDIK - Saputra, Samnur; Kosasih, Usep; Kusumaningtyas, Sarah (Bahasa Indonesia, 2024)
Students' lack of interest in learning mathematics has an impact on their memory of the material being taught. This is a challenge for educators to find the right learning method. So, it is necessary to develop learning methods with the help of games for arithmetic sequences and series. The aim of the research is to determine the feasibility, retention power and interest in learning after learning mathematics assisted by Math Maze on arithmetic sequences and series. The research method used is Design Research (DR) with an ADDIE design. Data was obtained through media expert validators and material experts as well as students. Data collection techniques include validation sheets, post-test and re-test, distributing questionnaires, and interviews. From the validation results, Math Maze is categorized as valid, retention power is categorized as high, and interest in learning is categorized as very high.